Perencanaan Embung Konservasi Di Taman Rusa Universitas Lampung - Cindy, Amelia Sukma; Purwadi, Opik Taufik; Welly, Margaretta; Herison, Ahmad (Universitas Lampung, 2019)
University of Lampung has some of water patch such as small dams and retention basin which is needed optimalisazion to improve the function. Among of the small dams, there is small dam is located at Deer Park at University Of Lampung need to redesign. The purpose of redesign this small dam conservation is to increase its function as water conservation building. Water conservation building has functioned as rain harvesting and water reserves during the dry seasonThe methods are used to redesign this small dam conservation are hydrological , small dam conservation construction planning , analysis stability of planned constructions and the last method is estimating building construction cost. Small dam conservation planned height of 5 m,withabaseelevationat+104,7 thedamcrestelevation+112,5,00m.The flood debit of 426,279 m3/sec with cycle period 10 years.Spillway which used is Open Ogee type and basin specific energy building Vlugter type. Stability small dam conservation at Deer Park University of Lampung construction stated as safe. Cost estimated of design planning of conservation small dam is Rp. 5.918.096.000,00. Reservoir volume after planned to be 13.213,5627 m3. This volume has increased from the existing volume of the previous reservoir, which was only 5.981,3997 m3. It can be concluded, the ability of small dam conservation to rain harvesting and water reserves during the dry season increases. Keyword : Small dam, Conservation, University of Lampung